LITERACY ABILITY USING PICTURE STORYBOOK MEDIA IN INDONESIAN LANGUAGE LEARNING CLASS IV SDN 90 PALEMBANG - Dinda Mutia; Kabib Sholeh; Sylvia Lara Syaflin (SMART: Journal of Multidisciplinary Educational, 2023)
The purpose of this study was to determine students' literacy skills using picture story books in Indonesian language learning class IV SDN 90 Palembang. The problem in this study was to determine students' literacy skills using picture story books. The research method used was descriptive qualitative. The data collection technique used observation of the homeroom teacher of class IV.B and students of class IV.B, documentation in the form of photographs during the research, interviews with class IV.B teachers and students of class IV.B and questionnaires which were distributed to 33 students and documentation of students reading picture story books in class. The result of distributing the questionnaire was that the average result of the questionnaire respondents was 98.29%.. On average, the whole can read and understand picture story books fluently, but there are not a few students who are not yet fluent in reading or still spell words, especially 3 male students who are still spelling when reading picture story books. Keyword:  literacy skills, picture story book media